2007
DOI: 10.2131/jts.32.411
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity Screening After Repeated Dose of a Newly Developed Oral Heparin Derivative in Male Cynomolgus Monkeys

Abstract: -Toxicity screening of a newly developed oral heparin derivative was carried out in twelve male cynomolgus monkeys (Macaca fascicularis), composed of three treatment and vehicle control groups. A newly orally active heparin derivative, developed by Seoul National University, was given to the treatment group at three doses with low (12.8 mg/kg), medium (89.6 mg/kg) and high (640 mg/kg) doses for 14 days. A treatment group did not show any change in body weights, hematological parmeters (e.g., RBC, WBC, platelet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…APTT, TT, and PT are routinely measured to assess blood coagulation in toxicity studies of anticoagulants. 24,25 The results of the coagulation tests conducted here showed no significant change between the coagulation function of the two groups. Although the APTT of the exosome group was significantly higher than that of the control group on day 7 and day 14, there was no significant difference between the two groups before and after each time point.…”
Section: Discussionmentioning
confidence: 52%
“…APTT, TT, and PT are routinely measured to assess blood coagulation in toxicity studies of anticoagulants. 24,25 The results of the coagulation tests conducted here showed no significant change between the coagulation function of the two groups. Although the APTT of the exosome group was significantly higher than that of the control group on day 7 and day 14, there was no significant difference between the two groups before and after each time point.…”
Section: Discussionmentioning
confidence: 52%
“…Furthermore, in this acute toxicity study, no other anticoagulant-related toxic changes in hematology and clinical chemistry were detected apart from the slight local swelling, the increase of TT, PT and APTT and the decrease of Fib after EH administration whose alterations ascribed to the pharmacodynamics of EH and were described in our preclinical animal thrombosis models (Liu et al, 2022a(Liu et al, , 2022b. APTT, TT and PT are routinely measured to assess blood coagulation in toxicity studies for anticoagulants (Kim et al, 2007;Kurata and Horii, 2004). Slight local redness and swelling at the injection site after administration suggested that there was minor bleeding at the injection site and it should be paid close attention in future clinical practices.…”
Section: Discussionmentioning
confidence: 71%
“…Therefore, there is a huge obligation for the development of an oral LMWH formulation (Hoffart et al 2006). Various strategies have been explored by researchers including use of penetration enhancers (Hayes et al 2006), microparticles (Javot et al 2009), polymeric nanoparticles (Chen et al 2009), dendrimeric nanocarriers (Bai and Ahsan 2009), chemical conjugates (Kim et al 2007a), biomimetic solid lipid nanoparticles (Paliwal et al 2011), alginate coated chitosan core shell nanoparticles (Bagre et al 2013), nanoparticles in enterically coated tablets containing permeation enhancers (Goharzadeh et al), nanocapsules as nanocarriers (Ramadan et al 2011), etc. However, till date, no oral formulation of heparin exists in the market (Hwang et al 2012, Kim et al 2011.…”
Section: Introductionmentioning
confidence: 99%